PENGARUH QUALITY OF WORK LIFE DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. AGUNG SEJAHTERA BHAKTI KABUPATEN KUTAI TIMUR - Jhoni Susanto; Ardi Paminto; Sri Wahyuni (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this research was to determine the influence of Quality of Work Life and the effect of job satisfaction on employee performance. The hypothesis put forward in this study that the Quality of Work Life and work kepusasan influence on the performance of employees of PT. Bhakti Agung Sejahtera East Kutai.Statistical analysis tool used is multiple linear regression analysis, with the formula Y  =  a  +  b1X1 + b2X2 + e. Based on the calculation result Y   =   0,808 + 0,283 X1+ 0,301 X2 + e.Based on test results using SPSS program, it can be concluded that the Quality of Work Life and job satisfaction affect the performance of employees of PT. Bhakti Agung Sejahtera East Kutai. Keywords : Quality Of Work Life, Job Satisfaction, Performance